Inquiry Models STEM in Physics Education for Innovative Learning Paradigm: Bibliometric Analysis Research - Setiani, Rahyu; Dawana, I R; Dwikoranto, D; Zuhro, Putri Fatimatuz (Studies in Learning and Teaching, 2024)
The aim of this research was to investigate research trends on Inquiry STEM topic in the context of physics education and conduct a bibliometric analysis to understand the development of research in this domain. Data were collected from the Scopus database using keywords relevant to Inquiry STEM and physics. The approach used in the analysis was the bibliometric method by utilising the Scopus database and VOSviewer, which resulted in 62 relevant documents. The results showed that the use of Inquiry STEM in physics education has become an increasingly popular topic over the past ten years, despite fluctuations in publication rates. This indicates potential challenges that need to be further explored in the future. Further research of Inquiry STEM in physics education could be helpful in improving students' critical thinking skills and motivation, given the evidence that this instructional model has demonstrated effectiveness in improving students' problem-solving abilities, critical thinking, and motivation. However, it's worth noting that this research has limitations due to its sole reliance on one database, namely Scopus, for data collection. Therefore, it is advisable for future research on Inquiry STEM in physics education to incorporate the utilization of other databases besides Scopus to ensure a broader range of data is considered.